“Control biológico de verticillium dahliae patógeno de cacao (theobroma cacao), con aislamientos de trichoderma spp endófilito” - Viena Bardales, Jack Flavio (2015)
Verticillium wilt caused by Verticillium dahliae L., is an important disease of cocoa and it is difficult to control, and it is difficult to control, because the pathogen survives hold on the soil, and chemical treatments are ineffective. Biological control is an alternativa solution to the overuse of pesticidas and reduces environmental contamination. Still, the fungus Trichoderma sp., an efficient biological control because of its ability to coloniza substrates rapidly, induce systemic acquired resistance in plants, plant growth promoting and possess antagonistic activity against a broad range of pathogenic fungi. This work was carried out to determine the effect of endophyte Trichoderma insolates in the control of Verticillium dahliae L., pathogen of Theobroma cacao. We used 24 isolates of seven species belonging to TE with reference to being biocontrols, which were provided by the Pathology Laboratory of ICT. were tested of antibiosis and mycoparasitism, to determine the in vitro antagonistic ability of endophyte Trichoderma spp (ET) on V. dahliae, for which there was antifungal secondary metabolites of Trichoderma spp., MIN broth to assess the percentage of mycelial inhibition of the pathogen, and use the method of pre-colonized petri dishes to assess the percentage of colonization of Trichoderma spp., to the pathogen. The metabolites obtained from isolates of ET- 83, ET-84 and ET-91 were those that completely inhibited of V.dahliae mycelial growth, followed by ET-7 and ET-20 with 61,21% and 60,49% respectively. However, ET-74 and ET-39 had no effect in controlling thepathogen. Mycoparasitism in testing, the isolates completely colonizad cultures ofV. dahliaewere ET-7, ET-84, ET-91, ET-20, ET-83, ET-102, ET-54, ET-56, ET116, ET-108 and ET-87, followed by ET-6 colonization with 63,33%, compared with other isolates that colonized ET less than 60%. In the test in greenhuose biocontrol, the ET-54 was isolated which reduced the disease higher with values of 20% incidence and severity 11,65 %; followed ET and ET-3 and ET-7 with valued incidence 50 and 40% respectively, and severity values with 22,51 and 23,41 % respectively comparaed to Control 1 treatment that received incidence and severity values of 100 and 60. 17 % respectively. While the isolates producing more root growth were TE-84 and ET-91 with 1083,5 and and 1046,02 cm respectively, compared with other isolates. in terms of dry biomass, isolates ET-3 and ET-91 were those that generated greater air dry weight (OW-A) with values of 3,96 and 3,81 grams respectively, while, ET-54, ET -97 and ET-3 isolates were producing more root dry biomass (DW-R) with 1,21; 1, 18 and 1, 17 grams respectively, compared with other isolates and the control 1 that was in DW-A and DW-R average values of 3,67 and 1,01 grams respectively.